2020
DOI: 10.3390/molecules25102269
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of a Tetrameric Type II β-Carbonic Anhydrase from the Pathogenic Bacterium Burkholderia pseudomallei

Abstract: Carbonic anhydrase (CA) is a zinc enzyme that catalyzes the reversible conversion of carbon dioxide to bicarbonate and proton. Currently, CA inhibitors are widely used as antiglaucoma, anticancer, and anti-obesity drugs and for the treatment of neurological disorders. Recently, the potential use of CA inhibitors to fight infections caused by protozoa, fungi, and bacteria has emerged as a new research line. In this article, the X-ray crystal structure of β-CA from Burkholderia pseudomallei was reported. The X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…[23][24][25] These roles have made CAs prime drug targets as FDA-approved carbonic anhydrase inhibitors are used to treat various disorders including glaucoma, 26,27 as a diuretic for kidney health, 28 treatment for congestive heart failure, 29 and recently certain isoforms have gained momentum as promising cancer targets. [30][31][32] Aside from human targets, CAs have been identified in a handful of parasites and pathogenic bacteria, 33,34 including Vibrio cholera, 35 Burkholderia spp 36,37 and N. gonorrhoeae. In bacteria, altering bicarbonate homeostasis was revealed to perturb the proton motive force and reduce bacterial fitness.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] These roles have made CAs prime drug targets as FDA-approved carbonic anhydrase inhibitors are used to treat various disorders including glaucoma, 26,27 as a diuretic for kidney health, 28 treatment for congestive heart failure, 29 and recently certain isoforms have gained momentum as promising cancer targets. [30][31][32] Aside from human targets, CAs have been identified in a handful of parasites and pathogenic bacteria, 33,34 including Vibrio cholera, 35 Burkholderia spp 36,37 and N. gonorrhoeae. In bacteria, altering bicarbonate homeostasis was revealed to perturb the proton motive force and reduce bacterial fitness.…”
mentioning
confidence: 99%
“…Aside from human targets, CAs have been identified in a handful of parasites and pathogenic bacteria, , including Vibrio cholera , Burkholderia spp , , and N. gonorrhoeae . In bacteria, altering bicarbonate homeostasis was revealed to perturb the proton motive force and reduce bacterial fitness .…”
mentioning
confidence: 99%
“…Within a general research project aimed at developing new anti-melioidosis drugs, we have undertaken a detailed characterization of these two enzymes. In particular, both enzymes were produced in Escherichia coli and kinetically characterized, showing to be moderately active in catalyzing the CO 2 hydration reaction (k cat = 1.6·10 5 s −1 , k cat /K m = 3.4·10 7 M −1 s −1 for BpsβCA and k cat = 5.3·10 5 s −1 , k cat /K m = 2.5·10 7 M −1 s −1 for BpsγCA) [38] , [39] , [40] ; furthermore their inhibition profile with different classes of molecules was deeply investigated [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] . However, while the crystallographic structure of BpsβCA was determined [38] , to date any structural information on BpsγCA is missing.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, both enzymes were produced in Escherichia coli and kinetically characterized, showing to be moderately active in catalyzing the CO 2 hydration reaction (k cat = 1.6·10 5 s −1 , k cat /K m = 3.4·10 7 M −1 s −1 for BpsβCA and k cat = 5.3·10 5 s −1 , k cat /K m = 2.5·10 7 M −1 s −1 for BpsγCA) [38] , [39] , [40] ; furthermore their inhibition profile with different classes of molecules was deeply investigated [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] . However, while the crystallographic structure of BpsβCA was determined [38] , to date any structural information on BpsγCA is missing. Here we completed the characterization of this enzyme investigating on its catalytic activity at different pH values, reporting its crystallographic structure and dissecting the role of residues involved in the catalytic mechanism by means of theoretical pKa calculations.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, β-CAs may represent an interesting target for finding anti-infectives with a novel mechanism of action 16 . Accordingly, Flaherty’s group 17 recently reported that sulphonamide CA inhibitors (CAIs), structurally related to acetazolamide (AAZ), have potent anti-bacterial effects against pathogenic drug resistant bacteria (which normally contain α-, β-, γ- and/or ι-CAs) 18 , 19 . They demonstrated this effect in vancomycin-resistant enterococci, validating thus in vivo the bacterial CAs as drug targets 16–17 .…”
Section: Introductionmentioning
confidence: 99%